Impact of Perceived Brand Dimensions on Consumers’ Purchase Choices - Mohammad, Anber Abraheem Shlash; Khanfar, Iyad A.A; Al- Daoud, Khaleel Ibrahim; Odeh, Mahmoud; Mohammad , Suleiman Ibrahim; Vasudevan, Asokan (Journal of Ecohumanism, 2024)
In the current research, the objective is to investigate the many aspects of brands that influence the purchasing decisions of consumers. A total of 470 questionnaires were delivered to participants who were in possession of cellular devices that were branded with the Samsung brand. The structural equation modeling approach was used in order to evaluate the study hypotheses. According to the findings of the research, there is a strong favorable influence of perceived brand name and perceived brand quality on consumer purchase choices. On the other hand, the study discovered that perceived brand price and perceived brand value have a negligible effect on a customer’s decision to make a purchase. In addition to the fact that several study possibilities have been found that may be of assistance to other researchers, the suggestions were produced with the intention of enhancing the function of the brand dimensions in order to profit from it in the marketing of cellular devices for both firms and consumers.